Generation of Immortalized Equine Chondrocytes With Inducible Sox9 Expression Allows Control of Hypertrophic Differentiation. Issue 5 (10th January 2017) - Gurusinghe, Saliya; Hilbert, Bryan; Trope, Gareth; Wang, Lexin; Bandara, Nadeeka; Strappe, Padraig
ABSTRACT: Immortalization of chondrocytes enables long term in vitro culture; however, the chondrogenic capacity of transformed cells varies, thus highlighting the need to develop a proliferative and tuneable chondrocyte cell line where hypertrophic differentiation can be controlled. In this study the SV40 large T antigen and human telomerase reverse transcriptase were employed to immortalize pooled equine chondrocytes through lentiviral vector mediated transduction either singly or on combination. Transformed chondrocytes proliferated stably over multiple passages, but resulted in significantly lower expression of chondrocyte specific collagen II mRNA ( P < 0.0001) and up regulation of the hypertrophic marker collagen X ( P < 0.0001) in three dimensional cultures. A Col2a1 promoter driven GFP reporter was constructed for real time monitoring of chondrogenic differentiation and a significant increase in promoter activation was observed in cultures treated with the growth factor TGFβ‐3 ( P < 0.05). To recapitulate the native articular chondrocyte phenotype we further transduced large T antigen immortalized chondrocytes with lentiviral vectors allowing either constitutive or doxycycline inducible expression of Sox9. In 3D cultures, the Sox9 over‐expressing chondrocytes secreted significantly higher levels of extracellular matrix polysaccharide glycosaminoglycan ( P < 0.05), while up‐regulating collagen II and Aggrecan mRNA ( P < 0.05) in both expression systems with a similar patterns observed with imunohistochemical staining. High levels of collagen X mRNA and protein were maintained with constitutive sox9 reflecting hypetrophic differentiation but significantly lower expression could be achieved with inducible Sox9. In conclusion, immortalization of equine chondrocytes results in stable proliferation but a reduction of chondrogenic potential whilst modulation of sox9 expression enabled control of hypertrophic characteristics. J. Cell. Biochem. 118: 1201–1215, 2017. © 2016 Wiley Periodicals, Inc. Abstract : In this study, the SV40 large T antigen and human telomerase reverse transcriptase were employed to immortalize pooled equine chondrocytes through lentiviral vector mediated transduction either singly or on combination. Transformed chondrocytes proliferated stably over multiple passages, but resulted in significantly lower expression of chondrocyte specific collagen II mRNA ( P < 0.0001) and up regulation of the hypertrophic marker collagen X ( P < 0.0001) in three dimensional cultures whilst modulation of sox9 expression enabled control of hypetrophic characteristics.